Prior workload has moderate effects on high-intensity match performance in elite-level professional football players when controlling for situational and contextual variables - Springham, M.; Williams, S.; Waldron, M.; Strudwick, A. J.; Mclellan, C.; Newton, R. U. (Journal of Sports Sciences, 2020)
This investigation examined the effect of prior workload on high-intensity football match performance. Player load variables were recorded using a global positioning system and converted into composite variables: rolling season accumulated load (AL), exponentially weighted moving average acute, chronic and acute:chronic workload ratio (A:C). Match-play high-intensity performance-per-minute: accelerations (ACC), sprints, high-speed running (HSR) and high metabolic load (HMLd) distances; and situational and contextual variables were recorded for all games. Partial least squares modelling, and backward stepwise selection determined the most parsimonious model for each performance variable. Quadratic relationships of small to moderate effect sizes were identified for sprint AL and sprint performance, HSR AL and HSR performance, acute HMLd and HMLd performance, acute sprint load and ACC performance and A:C sprint load and ACC performance. Match performance was typically greatest between the mean and +1SD. High chronic HMLd, and combined acceleration and deceleration (ACC+DEC) load exerted small beneficial effects on HMLd and HSR performance, whereas high acute load exerted trivial to moderate negative effects. High sprint A:C exerted a small beneficial effect on sprint performance and playing position exerted small effects on HSR and HMLd performance. Prior workload has trivial to moderate effects on high-intensity match performance in professional players.